Spiritual Entrepreneurship: Memaknai Spiritualitas Kerja Kristen - Ignatius Bambang Sukarno Hatta; Romi Lie (STTI Harvest Semarang, 2022)
The spirituality of work in secular circles is currently developing in such a way and mostly has a positive impact on the world of work itself, because of its nature which provides a balance between work and all its demands, with humans in their inner satisfaction and deepest desire to fulfill and serve the highest goals set forth. beyond existence. Efforts to explore the spirituality of Christian work have become an urgent need, not because they want to compete with the spirituality of work that is currently prevailing secularly, but as a form of fulfilling the Christian missionary call to